Single scan TROSY and E.COSY suite of experiments for the measurement of residual dipolar couplings in proteins. Issue 4 (2006) - Eliseo Eliseo, Tommaso Tommaso; Gallo Gallo, Mariana Mariana; Melis Melis, Riccardo Riccardo; Paci Paci, Maurizio Maurizio; Bazzo Bazzo, Renzo Renzo; Cicero Cicero, Daniel O. Daniel O.
Abstract : Simple modifications of the gradient enhanced version of the TROSY experiment allow to obtain four different spectra containing each one of the components of the H–N doublet in 15 N labelled proteins. By measuring the difference in peak position among these four spectra, residual dipolar coupling values can be obtained for medium sized proteins. This experiment, which exploits the use of pulse field gradients to select the 15 N coherence pathway, produces excellent results in terms of water suppression. Moreover, tuning of a single delay in the sequence reduces notably the presence of artifacts. The performance of this suite of experiments, that we called TEC (Trosy–E.Cosy) experiment, is tested against a J -modulation method, inherently more accurate but more time consuming, for the accuracy in the observed values of residual dipolar couplings. For larger proteins, the use of this strategy allows to select the most favourable combination of peaks giving the sharpest signals.